2010
DOI: 10.1038/nm.2248
|View full text |Cite
|
Sign up to set email alerts
|

A reductionist cell-free major histocompatibility complex class II antigen processing system identifies immunodominant epitopes

Abstract: Immunodominance is defined as restricted responsiveness of T cells to a few selected epitopes from complex antigens. Strategies currently used for elucidating CD4+ T cell epitopes are inadequate. To understand the mechanism of epitope selection for helper T cells, we established a cell-free antigen processing system composed of defined proteins: MHC class II, cathepsins, and HLA-DM. Our minimalist system successfully identified the physiologically selected immunodominant epitopes of model antigens, HA1 from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 37 publications
4
93
0
Order By: Relevance
“…18,22 Contradictory to CII predigestion data, nearly all rHA1-derived peptides were degraded by pre-exposure to cathepsins for 3h (Fig. 4a).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…18,22 Contradictory to CII predigestion data, nearly all rHA1-derived peptides were degraded by pre-exposure to cathepsins for 3h (Fig. 4a).…”
Section: Resultsmentioning
confidence: 87%
“…18 The system includes soluble purified HLA-DR (DR), CatB, CatH, and CatS that process protein antigens into peptides, and DM. Mass spectrometry is used for sequencing the unique peaks derived from each protein.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, DM acts as a peptide editor to catalyze the exchange of CLIP and other peptides onto MHC II during antigen presentation (810). We and other researchers have shown that DM-mediated peptide exchange plays a key role in epitope selection by favoring the presentation of peptides with higher kinetic stability (12, 1517, 23, 24). DM deficiency results in predominant accumulation of MHC II-CLIP complexes at the cell surface and defective peptide loading and exchange, leading to defective negative selection, increased self-reactivity and immunodeficiency (2527).…”
Section: Introductionmentioning
confidence: 94%
“…A similar methodology that was used to identify T cell epitopes presented by HLA-DR1 was recently described (33). In this study a system for cell-free Ag processing was established.…”
Section: Discussionmentioning
confidence: 99%